2023
DOI: 10.20944/preprints202305.1014.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Emergence of a New Strain of DENV-2 in South America: Introduction of the Cosmopolitan Genotype through the Brazilian-Peruvian Border

Abstract: We hypothesize the possible route of introduction of the cosmopolitan DENV-2 genotype into Brazil through the border with Peru. The five sequences presented in this study create a geographical link with the three others sequences of this genotype already recorded on the continent.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
2
1
0
Order By: Relevance
“…Finally, in other states including AM and RS, where genomic surveillance detected recent introductions of DENV-2-GII in 2022, DENV-1 was responsible for most dengue cases in the whole period supporting that DENV-2-GII only caused localized outbreaks in those states. In fact, in 2022, DENV-1 was responsible for more than 80% of the dengue cases in 17 out of 25 Brazilian states with data available.In summary, this study confirms that DENV-2-GII is circulating nationally in Brazil, expanding the findings of previous localized studies6,7 . Our phylogenetic analysis unveiled multiple introductions of this genotype into Brazil from Peru, generating multiple clades that spread in the country with different success.…”
supporting
confidence: 89%
See 2 more Smart Citations
“…Finally, in other states including AM and RS, where genomic surveillance detected recent introductions of DENV-2-GII in 2022, DENV-1 was responsible for most dengue cases in the whole period supporting that DENV-2-GII only caused localized outbreaks in those states. In fact, in 2022, DENV-1 was responsible for more than 80% of the dengue cases in 17 out of 25 Brazilian states with data available.In summary, this study confirms that DENV-2-GII is circulating nationally in Brazil, expanding the findings of previous localized studies6,7 . Our phylogenetic analysis unveiled multiple introductions of this genotype into Brazil from Peru, generating multiple clades that spread in the country with different success.…”
supporting
confidence: 89%
“…Here we present new data on the DENV- 1) which were aligned with a DENV-2-GII representative global dataset. Maximum likelihood phylogenetic analysis revealed that all DENV-2-GII Brazilian genomes, from this and previous studies 6,7 , clustered in a monophyletic clade with sequences from Peru and Bangladesh (Supplementary Figure 1). Our To assess the potential of DENV-2-GII to spread and trigger relevant outbreaks in Brazil, we analyzed the dynamics of DENV serotypes' circulation in the country as identified through PCR tests by the laboratory surveillance and informed in the national system of diseases of compulsory notification (SINAN).…”
Section: Research Lettersupporting
confidence: 63%
See 1 more Smart Citation